Evaluation of the Prognostic Utility of the Postoperative Inflammatory Burden Index in Colorectal Cancer - Furukawa, Shunsuke; Hiraki, Masatsugu; Kimura, Naoya; Kohya, Naohiko; Sakai, Masashi; Ikubo, Akashi; Samejima, Ryuichiro (Journal of Coloproctology, 2025)
This study aimed to evaluate the significance of the postoperative inflammatory burden index (IBI) as a prognostic marker and to investigate the clinical outcomes of patients with stage II and III colorectal cancer who underwent colorectal surgery.This retrospective study included 223 patients who underwent colorectal surgery for stage II and III colorectal cancers. The patients were divided into four groups based on postoperative IBI on days 1 and 7 (high or low): Group 1 (low & low, n = 118), Group 2 (high & low, n = 18), Group 3 (low & high, n = 56), and Group 4 (high & high, n = 31). The clinical impact of the postoperative IBI on recurrence-free survival (RFS) and overall survival (OS) was also evaluated.High postoperative IBI was significantly associated with decreased RFS and OS. The Kaplan-Meier survival curves for RFS and OS in stage II and III colorectal cancer showed a decline in Groups 2, 3, and 4, with a more pronounced decline observed in Group 4 (p = 0.001 and p = 0.007, respectively).This study suggests that the postoperative IBI may be a prognostic marker for RFS and OS in patients with stage II and III colorectal cancer. When postoperative IBI on days 1 and 7 is high, these findings may indicate a high-risk factor for the recurrence of colorectal cancer. Postoperative IBI is useful in establishing postoperative oncological surveillance and adjuvant chemotherapy strategies.
Keywords: Inflammatory burden index; colorectal cancer; stage II and III; postoperative